Optimization of heat supply for production facilities for building materials, products and structures - Abishev, Bekzat (Рroblems of engineering and professional education, 2023)
At present, about a thousand small and large enterprises for the production of building materials, products and structures are operating in Kazakhstan, and all of them are faced with the main problem, this is optimization of heat supply in the production hall or premises during the cold period of the year. In the absence of a comfortable temperature, the productivity drops by 10-15 percent as the classic ribbed heating pipes can not completely compensate for the lost heat at forty degree frost. To solve this problem, it is necessary to rationally organize heat supply, use combined heat supply, obtain cheaper heat of high potential and provide devices for autonomous regulation of coolant parameters with economic expediency. This article shows the results of research on the use of equipment necessary to optimize the heat supply of the production facilities for building materials, products and structures.